Nature-derived microneedles with metal-polyphenolic networks encapsulation for chronic soft tissue defects repair: Responding and remodeling the regenerative microenvironment - Chengyang Zhu; Zun Fan; Zhijie Cheng; Jun Yin; Lei Qin; Xin Zhao (Materials Today Bio)
The treatment outcomes of traditional patches for chronic soft tissue defects (CSTDs) are unsatisfactory in clinical, owing to the lack of intrinsic bioactivities to orchestrate the intricate regenerative process. To tackle this deficiency, nature-derived microneedles (NMs) composed of silk methacrylate and snail mucus are developed in this study. The resultant NMs have excellent mechanical strength and biological adhesiveness, ensuring suture-free but reliable fixation on implanted site. To enhance the intrinsic bioactivities, metal-polyphenolic networks (MPNs) coordinated from copper (Cu) and curcumin (Cur) are designed and encapsulated into NMs. Cu-Cur MPNs harness the anti-oxidative and anti-inflammatory properties of Cur with the pro-angiogenic properties of Cu, targeting different negative aspects in CSTDs repair. Furthermore, the pH-responsive disassembly of Cu-Cur MPNs can respond to the acidic microenvironment, allowing for burst-free and on-demand drug delivery. Both in-vitro and in-vivo experiments demonstrate that NMs with Cu-Cur MPNs encapsulation (Cu-Cur-NMs) can restore redox homeostasis, reduce inflammatory response, and promote blood vessel formation, thus remodeling the regenerative microenvironment to greatly improve the repair quality of CSTDs. Therefore, the combined advantages of microneedles-based patch system and MPNs-based nanotherapeutic agent are explored for the first time, and our proposed Cu-Cur-NMs represent a multifunctional and promising device for CSTDs repair.